Perbedaan Tingkat Daya Juang dan Motivasi Berprestasi Siswa Ditinjau dari Pendapatan Orang Tua Saat Pembelajaran Daring selama Pandemi COVID-19 - Elni Yakub; Raudha Nurhidayah Al-Jannah; Rosmawati Rosmawati (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
: This study aims to determine the description and differences in fighting power and achieve- ment motivation of Junior High School in terms of their parents' income. This research uses quantitative methods with a comparative study. Data collection was carried out by means of a questionnaire to 164 students of junior high school. The results of this study indicate that the level of fighting power of stu- dents is mostly at a high level of fighting power of 50.6%. In addition, it was also found that the level of student achievement motivation was mostly at the high achievement motivation level of 45.1%. The re- sults of the unpaired t test show that there is a significant difference in the fighting power of students and the achievement motivation of students whose parents have high income and those who have low income during online learning during the COVID-19 pandemic.